2022
DOI: 10.1111/1471-0528.17066
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performance for placental dysfunction related stillbirth of the competing risks model for small‐for‐gestational‐age fetuses

Abstract: Objectives: To examine the predictive performance for placental dysfunction related stillbirths of the competing risks model for small-for-gestational-age (SGA) fetuses based on a combination of maternal risk factors, estimated fetal weight (EFW) and uterine artery pulsatility index (UtA-PI); and second, to compare the performance of this model with that of a stillbirth-specific model using the same biomarkers and with the Royal College of Obstetricians and Gynecologists (RCOG) guideline for the investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Although not quantified previously, it is perhaps unsurprising that the 35-37 weeks' competing-risks model for PE identifies risk for a broader range of pregnancy complications. Our competing-risks model for PE (at multiple gestational ages) 4 shares many predictors with our models for SGA 25,26 and stillbirth 27 , based on shared underlying placental pathophysiology 28 . The association of PE risk with both Cesarean section and NNU admission likely reflects diminishing placental reserve near or at term; term NNU admission most commonly results from perinatal asphyxia 29 .…”
Section: Interpretation Of Results and Implications For Clinical Prac...mentioning
confidence: 99%
“…Although not quantified previously, it is perhaps unsurprising that the 35-37 weeks' competing-risks model for PE identifies risk for a broader range of pregnancy complications. Our competing-risks model for PE (at multiple gestational ages) 4 shares many predictors with our models for SGA 25,26 and stillbirth 27 , based on shared underlying placental pathophysiology 28 . The association of PE risk with both Cesarean section and NNU admission likely reflects diminishing placental reserve near or at term; term NNU admission most commonly results from perinatal asphyxia 29 .…”
Section: Interpretation Of Results and Implications For Clinical Prac...mentioning
confidence: 99%
“…The first stage is screening for PE at 11-13 weeks' gestation and treatment of the high-risk group with aspirin; this is effective in the prevention of preterm PE as well as early SGA in the absence of PE [18][19][20][21][22][23] . The second stage is screening during the routine mid-trimester scan by a combination of maternal risk factors, estimated fetal weight and uterine artery pulsatility index, which identifies a high-risk group that contains a high proportion of placental dysfunction-related stillbirths that occur at 24-37 weeks' gestation; close monitoring of these pregnancies for early diagnosis of SGA fetuses may prevent at least some of such stillbirths by defining the best monitoring approach and timing of delivery 5,24,25 . The third stage is routine ultrasound examination at 36 weeks' gestation because screening at midgestation provides poor prediction of stillbirth at term; the detection rate for term SGA by assessment at 36 weeks' gestation is twice as high as with screening at midgestation 26,27 .…”
Section: Consequences For Clinical Practicementioning
confidence: 99%
“…We have reported previously that the risk for stillbirth has a U‐shaped relationship with maternal age and increases with increasing body mass index, black race, smoking, medical history of chronic hypertension and diabetes mellitus, and a history of previous stillbirth 5,6 . Studies from countries with populations that are of predominantly white race have consistently reported that, in women of black race, the incidence of stillbirth is 2‐fold higher than in white women; the risk for South or East Asians is usually not different from that in white women 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Royal College of Obstetricians and Gynaecologists guideline recommends using a risk-scoring system to identify the high-risk group 9 . We have demonstrated recently that this method, implemented at 22 weeks' gestation, has poor performance for the identification of a SGA neonate and stillbirth 10,11 . There is evidence that prediction of SGA is improved when, first, routine third-trimester biometry is used instead of selective sonography based on maternal risk factors and serial measurements of symphysis-fundus height 12 , second, EFW is used instead of fetal abdominal circumference 8,13 and, third, the scan is carried out at 36 weeks rather than at 32 weeks' gestation 8,14,15 .…”
Section: Introductionmentioning
confidence: 99%